Aplikasi Donasi Berbasis Mobile Menggunakan Metode Scrum (Universitas (STKIP) PGRI Sumatera Barat, 2022)
This study discusses the design and development of mobile-based applications based on literature studies by several previous researchers. Therefore, the purpose of this research is to overcome the problem of used goods being disposed of or stored by distributing them to those in need through community intermediaries and using technology. The method used in this study is the Scrum Framework by determining the product backlog, sprint planning, one week sprint, sprint review and sprint retrospective in this study. After the application has been developed, an analysis will be carried out on the use of the Scrum method in the application development stage. The result of this research is a mobile-based donation application that is useful as an intermediary platform for donors who want to donate some of their fortune and communities that help recycle or distribute donated items to those who need it more. For the implementation of this application, residents of the city of Batam are used for distribution of assistance to orphanages or foundations that care for people in need in the city of Batam, according to a questionnaire survey distributed to users or through interview methods as much as 87% are greatly helped by this application such as information the location of the orphanage, the need for goods and others.